Effect of Different Isometric Exercise Modalities on Myocardial Work in Trained Hypertensive Patients with Ischemic Heart Disease: A Randomized Pilot Study - Giuseppe Caminiti; Giuseppe Marazzi; Maurizio Volterrani; Valentino D’Antoni; Simona Fecondo; Sara Vadalà; Barbara Sposato; Domenico Mario Giamundo; Matteo Vitarelli; Valentina Morsella; Ferdinando Iellamo; Vincenzo Manzi; et al. (Journal of Functional Morphology and Kinesiology, 2025)
Background: Isometric exercise effectively reduces blood pressure (BP) but its effects on myocardial work have been poorly studied. For the present study, we compared acute changes in myocardial work during two different isometric exercises, namely, bilateral knee extension and handgrip, in patients with hypertension and underlying ischemic heart disease (IHD). Methods: This was a randomized pilot study in which 48 stable, trained patients with hypertension and IHD were enrolled. Patients were randomly assigned to perform a single session of bilateral knee extension (IKE) or handgrip (IHG) exercises or no exercise (control), with a 1:1:1 ratio. Both exercises were performed at 30% of maximal voluntary contraction and lasted three minutes. Echocardiography and BP measurements were performed at rest, during the exercise, and after ten minutes of recovery. Results: Both exercises were tolerated well, and no side effects occurred. During the exercise, the systolic BP increased significantly in the IKE group compared with the IHG and control groups (ANOVA p < 0.001). Left ventricular global longitudinal strain decreased significantly in the IKE group (−21%) compared with the IHG and control groups (ANOVA p 0.002). The global work index increased significantly in the IKE group (+28%) compared with the IHG and control groups (ANOVA p 0.034). Global constructive work and wasted work increased significantly in the IKE group compared with the IHG and control groups (ANOVA p 0.009 and <0.001, respectively). Global work efficiency decreased significantly in the IKE group (−8%) while remaining unchanged in the IHG and control groups (ANOVA p 0.002). Conclusions: Myocardial work efficiency was impaired during isometric bilateral knee extension but not during handgrip, which evoked a limited hemodynamic response.